After occupy: economic democracy for the 21st century - Malleson, Tom (Oxford, 2014)
"These days, it is easy to be cynical about democracy. Even though there are more democratic societies now (119 and counting) than ever before, skeptics can point to low turnouts in national elections, the degree to which money corrupts the process, and the difficulties of mass participation in complex systems as just a few reasons the system is flawed. The Occupy movement in 2011 proved that there is an emphatic dissatisfaction with the current state of affairs, particularly with the economy, but, ultimately, it failed to produce any coherent vision for social change. So what should progressives be working toward? What should the economic vision be for the 21st century?